Skrining Fitokimia dan Uji Potensi Ekstrak Buah Tembelakan (Lantara camara L.) Terhadap Pertumbuhan Bakteri Pseudomonas aerugininosa: Phytochemical Screening and Testing of the Potential of Tembelakan Fruit Extract (Lantara camara L.) Against the Growth of Pseudomonas aeruginosa - Haliza, Nur; Tahar, Musrifah; Hakim , Sufyan (Jurnal Sumberdaya Hayati, 2026)
Tembelekan (Lantana camara L.) is a natural plant resource with potential application as an antibacterial agent, especially in its fruit. The objective of this study was to determine the secondary metabolite content in methanol and n-hexane extracts of Tembelekan (Lantana camara L.) through phytochemical testing and to examine its potential as an antibacterial agent against the growth of P. aeruginosa bacteria using the well diffusion method with concentrations of 20%, 40%, 60%, 80%, and 100%, while the positive control used tetracycline and the negative control used distilled water. The results showed that the methanol extract contained secondary metabolites, namely tannins, alkaloids, and phenolics. Meanwhile, the n-hexane extract contained saponin compounds. Both methanol and n-hexane extracts had activity against the growth of P. aeruginosa bacteria with inhibition zone diameters of 11.5 mm and 6.16 mm at a concentration of 100%. These results were better than the positive control with an inhibition zone diameter of 10.3 mm.